Polyhedral oligomeric silsesquioxane-containing thiol-ene fibers with tunable thermal and mechanical properties - Fang, Yichen; Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2016)
Polyhedral oligomeric silsesquioxanes (POSS) are versatile inorganic-organic hybrid building blocks that have potential applications as reinforcement nanofillers, thermal stabilizers, and catalyst supports for metal nano particles. However, fabrication of fibrous materials with high POSS content has been a challenge because of the aggregation and solubility limits of POSS units. In this paper, we describe a robust and environmentally friendly fabrication approach of inorganic-organic hybrid POSS fibers by integrating UV initiated thiol-ene polymerization and centrifugal fiber spinning. The use of monomeric liquids in this approach not only reduces the consumption of heat energy and solvent, but it also promotes homogeneous mixing of organic and inorganic components that allows integration of large amount of POSS (up to 80 wt %) into the polymer network. The POSS containing thiol-ene fibers exhibited enhanced thermomechanical properties compared to purely organic analogs as revealed by substantial increases in residual weight and a factor of 4 increase in modulus after thermal treatment at 1000 degrees C. This simple fabrication approach combined with the tunability in fiber properties afforded by tailoring monomer composition make POSS containing thiol-ene fibers attractive candidates for catalyst supports and filtration media, particularly in high-temperature and harsh environments.
Keywords: cross-linked fiber; enhanced thermomechanical properties; inorganic-organic hybrid fiber; POSS; reactive centrifugal spinning; thiol-ene photopolymerization